Two-sites’ spin chain as a good statistical representative of an infinite one - Pennini, Flavia Catalina (2021)
We apply information-theory based symbolic quantifiers, related to complexity studies, in order to investigate interacting spin chains, in which there is competition between one-body and two-body quantum interactions. Our system of reference is a well-known XY model with N-spins. We show that most of its thermal features can already be detected with N = 2.